Covalent modification of graphene and micro-diamond with redox active substrates via photogenerated carbenes. (April 2015) - Hesari, Mahdi; Workentin, Mark S.
Abstract: The surface of graphene (graphene oxide) and micro-diamond were modified with a tethered redox active ferrocene moiety through the photolysis of 3-(ferrocenyl-hexyloxy)-3-(trifluoromethyl)-diazirine (1 ). The tethered terminal diazirine group loses nitrogen on photolysis at 350 nm to generate a reactive carbene that then undergoes interfacial covalent bond formation with the inherent (or introduced) surface chemical functionalities on the carbon materials. The modified materials were characterized primarily by scanning electron microscopy–energy dispersive X-ray spectroscopy (SEM–EDX) analysis and cyclic voltammetry (CV) with comparison to dark/control studies. By comparison to the control studies the photo-modified graphene or micro-diamond–ferrocene hybrid materials are robust to repetitive washes and centrifugations, further supporting the covalent decoration of these carbon-based nanomaterials via carbene reactivity from photolysis of the diazirine template.